Sentiment analysis of halal food trends during COVID-19 - Nadia Nurul Izza; Mia Sari; Mughnii Kahila Shanty (Indonesian Journal of Islamic Economics Research, 2022)
Due to the pandemic of Corona Virus Disease (Covid-19), consumer awareness of halal products has increased. In this context, the government is also attempting to raise public knowledge about halal and thoyib products' growth and the halal industry's present trend. This study aims to ascertain public sentiment regarding halal food throughout the last four years, from 2019 to 2022. The method combines descriptive statistical analysis, meta-analysis, and sentiment analysis using secondary data in the form of metadata from 88 Scopus-indexed articles, then processed using Microsoft Excel 2019 and Senti Strength. This study discovered that the trend toward healthy halal food continued to grow throughout the pandemic, and the halal product market maintained a good performance. With the growth of the halal industry in the halal food and beverage sector, it is hoped that it will become a strong advocate for the SDGs, particularly the third goal, which aims to ensure a healthy life and promote prosperity while also assisting economic growth through the strengthening of the halal value chain, which is the primary strategy for accelerating sharia economic growth.